2019
DOI: 10.1101/778407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced antibacterial drug resistance and blaCTX-M β-lactamase gene carriage in cattle-associated Escherichia coli at low temperatures, at sites dominated by older animals and on pastureland: implications for surveillance

Abstract: 16Little is known about the drivers of critically important antibacterial resistance in 17 species with zoonotic potential present on farms (e.g. CTX-M ꞵ-lactamase-positive 18 Escherichia coli). There is also debate about the influence of farms on the circulation 19 of resistance in local human populations. This was a two-year surveillance study on 20 53 dairy farms. E. coli positive for blaCTX-M were detected in 224/4145 (5.4%) of all 21 samples from faecally-contaminated sites. E. coli positive for blaCTX-M … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…Of these, 4145 samples were positive for detectable levels of E. coli and 384 samples were positive for growth of CTX-R E. coli . 18 From these, 1226 colonies were taken forward for PCR testing for possible cephalosporinase genes of interest (GOIs): bla CTX-M (groups 1, 2, 8, 9 and 25), bla CMY , bla DHA , and bla SHV . Over half (648/1226; 52.7%) of all CTX-R isolates tested were found to harbour bla CTX-M genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 4145 samples were positive for detectable levels of E. coli and 384 samples were positive for growth of CTX-R E. coli . 18 From these, 1226 colonies were taken forward for PCR testing for possible cephalosporinase genes of interest (GOIs): bla CTX-M (groups 1, 2, 8, 9 and 25), bla CMY , bla DHA , and bla SHV . Over half (648/1226; 52.7%) of all CTX-R isolates tested were found to harbour bla CTX-M genes.…”
Section: Resultsmentioning
confidence: 99%
“…Details of farm sample collection and microbiological analysis has recently been reported. 18 In brief, samples of faecally contaminated sites were collected using sterile overshoes on 53 dairy farms located in South West England between January 2017 and December 2018. Samples were plated onto TBX agar (Sigma-Aldrich, Poole, UK) containing 16 mg/L cephalexin.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported a survey of resistant E. coli in faecal samples from 53 dairy farms in South West England. 23 Of 4145 faecal samples collected from vicinities near animals, 263 were positive for FQ-R E. coli , representing 49 of 53 farms surveyed. 23 Of 42 farms located within a 50 x 50 km region, which included the homes of the people providing the urinary samples discussed above, 245 FQ-R E. coli isolates from this earlier study 23 were taken forward for further analyses, representing one unique isolate from each positive sample.…”
Section: Resultsmentioning
confidence: 99%
“…23 Of 4145 faecal samples collected from vicinities near animals, 263 were positive for FQ-R E. coli , representing 49 of 53 farms surveyed. 23 Of 42 farms located within a 50 x 50 km region, which included the homes of the people providing the urinary samples discussed above, 245 FQ-R E. coli isolates from this earlier study 23 were taken forward for further analyses, representing one unique isolate from each positive sample. Multiplex PCRs showed that aac(6’)Ib-cr (found to be highly prevalent in the human urinary E. coli isolates) was entirely absent from the farm isolates and only nine isolates carried a PMQR gene (5 qnrS , 2 qnrA and 2 qnrD) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation